A Pharmacovigilance Study on Causality and Severity Assessment of Adverse Drug Reactions in a Teaching Hospital - Fatima, Mehruq; Daniel, Kothapally (Journal of Neonatal Surgery, 2025)
Objectives: The main purpose of the study is to assess the causality, severity, preventability of ADRs and factors associated with ADRs in chronic disease patients of tertiary care teaching hospital. Study setting and Design: A Prospective observational longitudinal study was conducted in a tertiary care teaching hospital at Hyderabad, India, for 3 years. Materials and Methods: Patients of age group > 18 years were included in the study. All the patients were distributed according to their gender, age, number medications used, disease condition and socioeconomic state. The reported ADRs were analyzed by WHO-UMC causality, Hartwig’s Siegel’s scale and modified Shumock and Thornton criteria respectively. Statistical analysis used: Descriptive statistical analysis was used. Results: A total of 691 patients enrolled in the study, in that 391 patients reported with 510 ADRs. Of these 37.0% are in-patients and 62.9% are out-patients. Majority of the patients are female category (58.0%) and 45.8% of ADRs reported from adults (41-60 years). 65.8% patients are non-adherent to medication. Life style habits, economic status and education are found to be predictors for ADRs. WHO-UMC scale showed 42.9% of ADRs probable. Hartwig’s and Siegel’s severity scales shown 13.1 % ADRs are severe followed by 33.7% moderate ADRs and 40% of ADRs were preventable. Conclusion: Hence our study advises that there is a need of improvement in ADR reporting from health care professionals. This study also suggests further research in India for the improvement of possible intervention strategies to reduce burden and cost of ADR.